ACADEMIC MENTAL HEALTH GALA: BRIDGING THE GAP - Zafar, Urooj; Mustafa, Ali Burhan (Journal of Pakistan Psychiatric Society, 2022)
According to a BBC report published in 2016, around 15 million people in Pakistan are struggling with psychiatric disorders of any cause. The irony of the fact is that the psychiatric patients of Pakistan are still in search of rights to treat as patients, chained or tied, swinging like a rolling stone between ancient cultural beliefs and modern psychiatric management (mhGAP).Department of Psychiatry & Behavioral Sciences (MH Rana), Sheikh Zayed Medical College/Hospital (SZMCH), Rahim Yar Khan has been a strong advocate of providing effective treatment to the mentally ailing community. As a part of efforts, Academic Mental Health Gala: Bridging the Gap was organized in Rahim Yar Khan on 06-07th March 2022. The academic mental health gala was organized by the Department of Psychiatry & Behavioral Sciences SZMCH in collaboration with the World Psychiatric Association, Pakistan Psychiatric Society, The Islamia University of Bahawalpur (RYK campus), Enabling Center IUB, Mind Health Movement, and Al-Mustafa Mental, Addiction, and Behavioral Health Services.